Explorations in Quantum Computing - Williams, Colin P. (Texts in Computer Science, 2011)
By the year 2020, the basic memory components of a computer will be the size of individual atoms. At such scales, the current theory of computation will become invalid. "Quantum computing" is reinventing the foundations of computer science and information theory in a way that is consistent with quantum physics - the most accurate model of reality currently known. Remarkably, this theory predicts that quantum computers can perform certain tasks exponentially faster than classical computers and, better yet, can accomplish "impossible" feats such as teleporting information, breaking supposedly "unbreakable" codes, generating true random numbers, and communicating with messages that betray the presence of eavesdropping. This widely anticipated second edition of Explorations in Quantum Computing explains the field from a fresh perspective, emphasizing lesser known quantum transforms, and practical applications of quantum algorithms and quantum information theory. The required mathematical machinery is developed systematically, and the students' knowledge tested through several end-of-chapter exercises. This easy-to-read, time-tested, and comprehensive textbook provides a unique perspective on the capabilities of quantum computers, and supplies readers with the tools necessary to make their own foray into this exciting field. Topics and features: Concludes each chapter with exercises and a summary of the material covered Provides an introduction to the mathematical formalism of quantum computing, and the quantum effects that can be harnessed to achieve unparalleled new capabilities Discusses the concepts of quantum gates, entangling power, quantum circuits, quantum Fourier, wavelet, and cosine transforms, quantum universality, quantum computability, and quantum complexity Examines the potential applications of quantum computers in areas such as search, code-breaking, solving NP-Complete problems, quantum simulation, quantum chemistry, and mathematics Describes uses of quantum information, including quantum teleportation, superdense coding, quantum data compression, quantum cloning, quantum negation, and quantum cryptography Reviews the advancements made towards practical quantum computers covering developments in quantum error correction, quantum error avoidance, and alternative models of quantum computation This text/reference is ideal for anyone wishing to learn more about this incredible, perhaps "ultimate," computer revolution. Dr. Colin P. Williams is Program Manager for Advanced Computing Paradigms at the NASA Jet Propulsion Laboratory, California Institute of Technology, and formerly acting Associate Professor of Computer Science at Stanford University where he taught courses on quantum computing and quantum information theory, and computer-algebra systems. He has spent over a decade working in quantum computing, and inspiring and leading high technology teams. Today his interests include quantum computing, artificial intelligence, cognitive computing, evolutionary computing, computational material design, computer visualization, and computationally-enabled remote olfaction. He was formerly a Research Scientist at Xerox PARC and a Research Assistant to Prof. Stephen W. Hawking at Cambridge University.